Factors determining the financial effectiveness of outsourcing in medical entities in Poland - Borowska, Mariola; Augustynowicz, Anna; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2018)
The aim of the paper was to analyze the financial efficiency of outsourcing in connection with basic and auxiliary activity of medical entities in Poland. Research material consisted of 755 questionnaires filled in by the representatives of medical entities. Five of them were completed only partially, and thus they were not qualified for analysis, which means that complete analysis was performed in 750 medical entities, selected at random from the Register of Health Care Providers. The analysis of medical entities was performed in connection with outsourcing activities. The following auxiliary services were examined: cleaning, laundry, catering, property security and waste disposal, together with the services connected with basic activity, such as: medical staff, medical imaging, laboratory diagnostics. Each area was analyzed in connection with the reason for transferring a given activity to an external company, benefits and disadvantages obtained in connection with separating the service from the entity’s structure as well as the method for monitoring the external company. Economies that medical entities gained compared to the costs of the same function before its separation were analyzed, together with the fact whether employees of the entity were given the job in the medical entity after its restructuring or not. All of the abovementioned areas were analyzed with relation to entity type, following the division into public and non-public entities.